Transcription factors Asg1p and Hal9p regulate pH homeostasis in Candida glabrata - Wu, Jing; Chen, Xiulai; Cai, Lijun; Tang, Lei; Liu, Liming (Frontiers in Microbiology, 2015)
Candida glabrata is an important microorganism used in commercial fermentation to produce pyruvate, but very little is known about its mechanisms for surviving acid stress in culture. In this study, it was shown that transcription factors Asg1p and Hal9p play essential roles in C. glabrata in the tolerance of acid stress, as the deletion of CgASG1 or CgHAL9 resulted in the inability to survive in an acidic environment. Cgasg1 and Cghal9 mutant strains are unable to maintain pH homeostasis, as evidenced by a decrease in intracellular pH and an increase in reactive oxygen species production, which results in metabolic disorders. The results showed that intracellular acidification was partly due to the diminished activity of the plasma membrane proton pump, CgPma1p. In addition, transcriptome sequencing revealed that Cgasg1 and Cghal9 mutant strains displayed a variety of changes in gene expression under acidic conditions, including genes in the MAPK signaling pathway, plasma membrane or cell wall organization, trehalose accumulation, and the RIM101 signaling pathway. Lastly, quantitative reverse-transcribed PCR and cellular localization showed that CgAsg1p and CgHal9p played independent roles in response to acid stress.